2018
DOI: 10.1007/s00384-018-3209-1
|View full text |Cite
|
Sign up to set email alerts
|

The growing discrepancy between resident training in colonic surgery and the rising number of general surgery graduates

Abstract: PURPOSE The decrease in resident operative experience due to working-hour directives and sub-specialization within general surgery is the subject of growing debate. This study aims to examine how the numbers of colectomies used for resident training have evolved since the introduction of workinghour directives and to place these results within the context of the number of new general surgeons. METHODS Based on the nationwide database of the Swiss association for quality management in surgery, all segmental col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Furthermore, about 25% of the index procedures have been performed by residents. While LCHE was expectedly the most frequent resident procedure and PPPD was not performed by surgeons in training, especially the low number of sigmoid resections is alarming and supports the data gained by Kaser et al [2], who have recently stated that fewer colonic surgeries are used for resident training. The authors also state that due to a trend toward specialization and the advancing complexity of the procedures, resident procedures are reduced.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, about 25% of the index procedures have been performed by residents. While LCHE was expectedly the most frequent resident procedure and PPPD was not performed by surgeons in training, especially the low number of sigmoid resections is alarming and supports the data gained by Kaser et al [2], who have recently stated that fewer colonic surgeries are used for resident training. The authors also state that due to a trend toward specialization and the advancing complexity of the procedures, resident procedures are reduced.…”
Section: Discussionsupporting
confidence: 57%
“…The creation of specialized surgical centers limits the availability of basic general surgical procedures in specialized centers and of complex surgeries in primary care hospitals. Furthermore, the European working time directive reduces the time residents spend in the hospital and the operating room (OR) and Kaser et al [2] further demand to better utilize surgical teaching opportunities and to re-structure surgical training. Surgical training needs to adapt to these changes, e.g., by using simulators to enable skill acquisition outside of the OR.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, surgical training in Switzerland includes abdominal general surgery as well as musculoskeletal trauma and many general surgeons in smaller, peripheral Swiss hospitals still perform a broad spectrum of surgical procedures, preventing adequate specialization. Additionally, the implementation of working hour directives and the increased number of surgical residents have resulted in a decreased exposure to colorectal surgery during surgical training, which might furthermore impact on learning of complex MIS techniques [51]. However, centralization with resulting increased caseloads at specialized centers may result in increased MIS amenability for rural and low-income populations in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal operations A study from Switzerland showed that less than 5% of all segmental colectomies between 2006 and 2015 were performed by residents [55]. During the same time period, the annual number of graduates increased by more than 100%.…”
Section: Literature Regarding Training In Gep-netmentioning
confidence: 99%